High Prevalence of Factor V Leiden in Healthy Jordanian Arabs - Awidi, A.; Shannak, M.; Bseiso, A.; Kailani, M. A. M.; Kailani, M. A.; Omar, N.; Anshasi, B.; Sakarneh, N. (Thrombosis and Haemostasis, 1999)
The prevalence of APC resistance in healthy Jordanian Arabs was studied. Between October 1996 through September 1997 a total of 400 healthy subjects were studied. There were 212 males and 188 females. APC resistance was studied by functional and DNA methods. There were a total of 52 subjects (13%) who were APC resistant by the functional test. There were 49 subjects (12.25%) who had FV Q506 by DNA test. Of these there were 42 heterozygous and 7 homozygous (allele frequency 0.07). None of the subjects had clinical thrombosis. It is concluded that the prevalence of APC resistance due to FV Q506 is high in Jordanian Arabs.